STUDENTS’ ATTITUDE AND TEAMWORK - Wibowo, Ari; Euis Happy Wangloan (Dinasti International Journal of Management Science, 2019)
This research has a purpose to give contribution about the effectiveness of gamification onchanging students’ attitude towards teamwork and attitude components in attitude toward teamwork. This study was designed to measure the effectiveness of the use of gamification, especially board game. The researcher collected the primary data by conduct experimental research with compare the result of before-after experiment. The tools that used for treatment is the Forbidden Island game. Then the questionnaire of pre-test and post-test that given as treatment refer to preliminary research for question guidelines components of attitude (affect, behavior and cognition) and for question guidelines of attitude toward teamwork. Gamification especially board game is one of method that popularly used in education world. However, the study that measure effectiveness of board game as apparatus for learning and achieve desirable attitude and behavior was still limited. Therefore, researcher conducted this research to prove whether the board game can achieve certain level of attitude toward teamwork and the components of attitude toward teamwork which is affect, behavior, and cognition. In order to answer the research objective, the results showed there was a significant difference between the pretest and posttest result after treatment for attitude toward teamwork and components of attitude toward teamwork.